Simulating the interaction of solitary wave and submerged horizontal plate using SPH method - Aghili, Mirhossein; Ghadimi, Parviz; Faghfoor Maghrebi, Yaser; Nowruzi, Hashem (International Journal of Physical Research, 2014)
In the current study, weekly compressible smooth particle hydrodynamics (WCSPH) method is implemented to simulate solitary wave interaction with horizontal submerged plate at four different vertical positions. To accomplish this task, MLS density filter is applied to reduce the pressure fluctuations. Moreover, Symplectic scheme with dynamic boundary particle (DBP) is considered. Free surface profile, pressure, and vertical component of the wave force on the horizontal plate parameters are computed in this study. The obtained numerical results of solitary wave and its interaction with a horizontal plate are compared against existing experimental data and very good compliance is achieved. CFD results indicate that as distance of the horizontal plate from free surface decreases, wave energy reduces significantly. On the other hand, with an increase in horizontal plate distance from the seabed, vertical component of wave force and its pressure component substantially decrease. Keywords: WCSHP; submerged horizontal plate; pressure; wave force; solitary wave.